2021
DOI: 10.1007/s11356-021-15337-9
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin-leucine arginine blocks vasculogenesis and angiogenesis through impairing cytoskeleton and impeding endothelial cell migration by downregulating integrin-mediated Rho/ROCK signaling pathway

Abstract: The main characteristic of eutrophication is cyanobacteria harmful algae blooms. Microcystin-leucine arginine (MC-LR) is considered to be the most toxic and most commonly secondary metabolite produced by cyanobacteria. It has been reported that MC-LR had potential vascular toxicity. However, the mechanism that MC-LR induced vascular toxicity is very limited and remain to be clari ed. The aim of this study was to evaluate the toxic hazard towards the vasculogenesis and angiogenesis of MC-LR. Its effects on vasc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The studies of invertebrates were not listed in the tables, but some studies on crustacea ( Penaeus monodon , Daphnia magna , Daphnia similis ) (Bownik and Pawlik-Skowrońska 2019 ; Ferrão-Filho and da Silva 2019 ) and on mollusca ( Elliptio complanata , Helix pomatia ) (Vehovszky et al 2012 ) have been performed. Recently, mass mortalities of sea otters (Miller et al 2010 ), dolphins (Brown et al 2018 ) and African elephants (Wang et al 2021a ) have been attributed to cyanotoxin poisonings, although confirmatory investigations into the elephant deaths are required. If cyanotoxins can cause the deaths of megafauna, it is clear that humans can also be endangered, inter-species variability being taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…The studies of invertebrates were not listed in the tables, but some studies on crustacea ( Penaeus monodon , Daphnia magna , Daphnia similis ) (Bownik and Pawlik-Skowrońska 2019 ; Ferrão-Filho and da Silva 2019 ) and on mollusca ( Elliptio complanata , Helix pomatia ) (Vehovszky et al 2012 ) have been performed. Recently, mass mortalities of sea otters (Miller et al 2010 ), dolphins (Brown et al 2018 ) and African elephants (Wang et al 2021a ) have been attributed to cyanotoxin poisonings, although confirmatory investigations into the elephant deaths are required. If cyanotoxins can cause the deaths of megafauna, it is clear that humans can also be endangered, inter-species variability being taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…These seemingly contradictory results suggested that MET plays different roles under different metabolic environments. To investigate the role of MET in damaged TM cells and ocular hypertension (OHT) mouse models, we used tert-butyl hydroperoxide (tBHP) to induce oxidative damage in TM cells ( Tang et al, 2013 ; Wang et al, 2021 ) and topical glucocorticoids to create OHT mouse models ( Li et al, 2021 ). The results showed that MET protected against cytoskeletal destruction in TM by activating the integrin/ROCK pathway and alleviated elevated IOP in steroid-induced OHT mouse models.…”
Section: Introductionmentioning
confidence: 99%
“…Excessive reactive oxygen species (ROS) in TM play an important role in the disruption of cytoskeletal integrity and apoptosis ( Hu, et al,2017 ), leading to pathological alterations in AHO and subsequent IOP rise ( Babizhayev and Bunin,1989 ; Sacca, et al,2016 ). To investigate the role of metformin in damaged TM cells and ocular hypertension (OHT) mouse models, we used tert-butyl hydroperoxide (tBHP) to induce oxidative damage in TM cells ( Tang, et al,2013 ; Wang, et al,2021 ) and topical glucocorticoids to create OHT mouse models ( Li, et al,2021 ). The results showed that metformin protected against cytoskeletal destruction in TM by enhancing the integrin/ROCK pathway and alleviated elevated IOP in steroid-induced OHT mouse models.…”
Section: Introductionmentioning
confidence: 99%